Analisis Analisis Potensi Daya Pada Pembangkit Unit 7 PLTA Tes - Firmansyah Adam Permana Agustian; Helmizar (UNIB Press, 2023)
Currently the need for electrical energy is increasing both for industrial and household needs, but until now a lot of electrical energy has been replaced by non-renewable resources (coal), which will run out if it continues to be used. Tes Hydroelectric Power Plant is one of the electrical energy generators that can be renewable. Among the several generating units in Tes Hydroelectric Power Plant, Tes’s hydroelectric power plant unit 7 is the most recent, having been inaugurated for the first time in 2014. The power potential that can be projected from this hydroelectric power plant unit 7 still needs to be looked at further. Therefore, this study aims to analyze the potential for electric power from the Tes’s hydroelectric power plant unit 7 from 01 July 2022 to 03 July 2022. In making observations about the analysis of the power potential at the Tes’s hydroelectric power plant unit 7, several methods are used. Such as observation of data for 3 days of operation from 01 July 2022 to 03 July 2022, literature study and several interview methods with field consultants. The value of the air discharge obtained from the use of air volume per day at the Tes’s hydroelectric power plant unit 7. On three days of observation, the Tes’s hydroelectric power plant unit 7 were able to produce the highest electrical energy on 03 July 2022, namely 100,722 kWh and the lowest was 99,808 kWh on 02 July 2022. In three days, the electric power that paid for the Tes’s hydroelectric power plant unit 7 reached 4173, 40 kW. The Tes’s hydroelectric power plant unit 7 can generate a daily net income of Rp. 105,689,588, - with a perkWh price of Rp. 1300, - and reduced by the basic cost of Rp. 244.81, -, from the sale of electrical energy.